Phytochemical Analysis of Papaya, Mengkudu, Cassava, and Pearl Grass Leaf Extracts as Natural Anti-Hyperglycemic Agents - Intan Edo Setiowati; Nafisah Nahla Aulia Putri; Eva Agustina; Risa Purnamasari; Nova Lusiana; Irul Hidayat (International Conference on Sustainable Health Promotion, 2025)
Hyperglycemia is a medical condition in which blood glucose levels exceed normal limits, and is a characteristic feature of diabetes mellitus (DM). This disease is characterized by high blood sugar levels due to impaired insulin production. This study aims to determine the effect of secondary metabolites contained in papaya leaf extract, noni leaf extract, cassava leaf extract, and pearl grass extract as antihyperglycemic agents. The research method used maceration with 70% ethanol solvent to obtain a thick extract, followed by phytochemical testing. This method also used a literature review to determine the effect of bioactive compounds in cassava leaf extract (Manihot esculenta), noni leaf extract (Morinda citrifolia), papaya leaf extract (Carica papaya), and pearl grass extract (Hedyotis corymbosa) as natural hyperglycemia agents. The results showed that the four extracts contained various secondary metabolites, namely flavonoids, alkaloids, tannins, phenolics, saponins, steroids, and triterpenoids. Papaya leaves had the best extract with complete secondary metabolites to overcome hyperglycemia. Although the three extracts, namely cassava, noni, and pearl grass, did not have complete secondary metabolite content like papaya, they contained flavonoids, phenolics, saponins, and alkaloids to treat hyperglycemia. Thus, these local plants have the potential to be developed as sources of raw materials for natural hyperglycemia phytopharmaceuticals.